If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 4x + 3(-3x) Remove parenthesis around (-3x) 2 = 4x + 3 * -3x Multiply 3 * -3 2 = 4x + -9x Combine like terms: 4x + -9x = -5x 2 = -5x Solving 2 = -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 2 + 5x = -5x + 5x Combine like terms: -5x + 5x = 0 2 + 5x = 0 Add '-2' to each side of the equation. 2 + -2 + 5x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = 0 + -2 5x = 0 + -2 Combine like terms: 0 + -2 = -2 5x = -2 Divide each side by '5'. x = -0.4 Simplifying x = -0.4
| 4(w-2)=4w+2-3(-2w-2) | | .5(8x+6)+.1111111111(63x+45)= | | 6(3+3m)=-4m+8(4m-4) | | ln(x)-x=ln(y/2) | | 3a+2b=15 | | 2n-32=8(n-7) | | 11n-12-10n-1=-11 | | 2-4+=0 | | 45=X*N-5N^2 | | y^4+10=0 | | -2+-1x=-8x+2x | | -7(v-3)+7(-2+v)=4 | | 5iz-2i-4z+7=0 | | 8-18=30 | | 15-3m=-1 | | -sin^2x-2sinx-3=0 | | g-4.5=7.2 | | -32-8p=-2(3p-8)-8p | | 3m+18=4m+8 | | -2(5x+-1)=-18 | | 0=x^2-x-40 | | Y+2.7=2.6 | | 5iz-2i+4z+7=0 | | 2h=6.8 | | 2p+4q+6r=34 | | 5/2x=15/8 | | 4p-6q-2r=-2 | | t/7-2=14 | | 10p+2q+4r=64 | | x^2+6x+11=0.5x+3 | | 3y=-12x-36 | | t/7-2=16 |